ANALYSIS OF PRICE VARIATIONS AND INTEGRATION OF BROILER CHICKEN EGGS MARKET IN WEST SUMATRA - Putri, Mega Amelia; Yelfiarita, Yelfiarita; Afrizal, Roni; Arnayulis, Arnayulis (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
Chicken eggs are one of the primary sources of protein for people in West Sumatra. The level of consumption continues to increase every year, while the availability of broiler eggs is not stable. This condition illustrates the problems faced by consumers and producers, namely price instability. Market integration is a metric that demonstrates how price changes in the reference market affect price changes in the follower market. The objective of this research is to examine the price variation and market integration of broiler eggs in West Sumatra. Coefficient of variation analysis is used to examine price variation, while cointegration analysis with the Vector Autoregression (VAR)/Vector Error Correction Model (VECM) model is used to investigate market integration. The variations coefficient analysis shows that the price of chicken eggs on the market is relatively more stable than that of the consumer market. The results of the integration analysis show that there is no integration between the market for broiler eggs at the producer and consumer levels, both in the long and short term. This is due to the information asymmetry between the two markets.